In situ and in vitro comparison of laser fluorescence with visual inspection in detecting occlusal caries lesions - de Paula, Andreia Bolzan; Duarte Bonini Campos, Juliana Alvares [UNESP]; Diniz, Michele Baffi [UNESP]; Hebling, Josimeri [UNESP]; Rodrigues, Jonas Almeida (Springer London Ltd, 2011)
The aim of this study was to compare the in situ and in vitro performances of a laser fluorescence (LF) device (DIAGNOdent 2095) with visual inspection for the detection of occlusal caries in permanent teeth. Sixty-four sites were selected, and visual inspection and LF assessments were carried out, in vitro, three times by two independent examiners, with a 1-week interval between evaluations. Afterwards, the occlusal surfaces were mounted on the palatal portion of removable acrylic orthodontic appliances and placed in six volunteers. Assessments were repeated and validated by histological analysis of the tooth sections under a stereomicroscope. For both examiners, the highest intra-examiner values were observed for the visual inspection when in vitro and in situ evaluations were compared. The inter-examiner reproducibility varied from 0.61 to 0.64, except for the in vitro assessment using LF, which presented a lower value (0.43). The methods showed high specificity at the D(1) threshold (considering enamel and dentin caries as disease). In vitro evaluations showed the highest values of sensitivity for both methods when compared to the in situ evaluations at D(1) and D(2) (considering only dentinal caries as the disease) thresholds. For both methods, the results of sensitivity (at D(1) and D(2)) and accuracy (at D(1)) showed significant differences between in vitro and in situ conditions. However, the sensitivity (at D(1) and D(2)), specificity and accuracy (both at D(1)) of the methods were not significantly different when the same condition was considered. It can be concluded that visual inspection and LF showed better performance in vitro than in situ.
Keywords: Laser fluorescence; DIAGNOdent; Caries detection; Visual inspection; Occlusal caries